Suppressing the financing of terrorism : a handbook for legislative drafting - International Monetary Fund - legal dept. (Washington, D.C. : International Monetary Fund, Legal Dept., 2003)
This handbook is intended to facilitate the delivery of legal technical assistance in the CFT area.It provides essential legal materials and extensive background information to officials who are responsible for drafting legislation designed to combat the financing of terrorism.
Includes bibliographical references (p. 161-163).
aug 23/05/13
Loans
Keywords: Terrorism - prevention; Terrorism; International law